Collaborative Mentoring for In-service Teachers’ Well-being in the Nepalese Context - Dahal, Gyanu (Journal of NELTA Gandaki, 2023)
Teachers experience challenges in their teaching careers these days. The challenges sometimes may affect their personal and professional well-being. Therefore, to address these issues, teachers need to develop collaborative relationships with other teachers and engage in self–reflection activities. This study aims to explore the usefulness of building collaborative relationships through collaborative mentoring for teachers’ emotional and mental well-being. A review of selected literature examines collaborative mentoring as beneficial for teachers’ well-being as it enables teachers to reflect on their classroom practices and provide and receive support and feedback from their colleagues. I used a qualitative research paradigm to study the impact of collaborative mentoring on the emotional and mental well-being of six private school teachers. The data was collected from teachers' reflective journals and semi-structured interviews. The results seem to indicate collaborative mentoring is useful for teachers' mental and emotional well-being as well as professional development. This study is useful for those who are planning to research mentoring and collaborative mentoring, teachers' well-being, and teacher education.